THE ROLE OF POLITICAL PARTIES ON POLITICAL DEVELOPMENT IN AFRICA CASE STUDY OF SOUTH SUDAN - Dr. Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The purpose of this study was to investigate the Role of Political Parties towards Political Development in South Sudan. The study did not reach entire South Sudan but individuals from selected areas were taken to represent the population. The officials of South Sudan Council of Political Parties. The study identified the possible ways through which Political Parties could facilitate the Public awareness about Political Development in South Sudan. The study established which Political Parties Participation play significance role in political development and what is their influence among communities of South Sudan. The research design adapted in this study was survey in which the researcher went to the field to collect data directly. Sample size in this study was 50 respondents here the researcher employed simple random sampling techniques to select 100 respondents from population. Questionnaires and interviews were used to collect data. Data analysis was presented in tables with emphasis to frequencies and percentages. The study establish that political parties play essential role in nation building and political development in South Sudan. The political party’s participation is seeking to improve the quality of livelihood and effective popular participation development activities are the major results in mutual benefits and share responsibilities the people of South Sudan. The study conclusion is to achieve the sets goals and the role of political parties’ participation should be ready to face difference kind of risks and challenges that they may encounter during their work.